Pengaruh Rating, Review Online, dan Harga terhadap Keputusan Pembelian pada Official Store Xiaomi di Tokopedia - Muhammad Syaffalutfi; Donant Alananto Iskandar (STREAMING, 2026)
This study aims to analyze the influence of ratings, Online Customer Reviews (OCR), and price on purchasing decisions at the Xiaomi Official Store on Tokopedia. A quantitative research approach was employed, involving 200 respondents selected through a non-probability sampling technique using purposive sampling. The sample size was determined by considering the maximum number of arrows directed toward a latent construct in the research model. Data were collected through online questionnaires and analyzed using multiple linear regression. The findings reveal that ratings, Online Customer Reviews, and price each have a significant positive effect on purchasing decisions. Furthermore, these variables simultaneously exert a significant influence on consumers’ buying decisions. The results suggest that consumers tend to rely on product ratings, customer feedback, and price considerations when making online purchases. Therefore, maintaining high product ratings, effectively managing customer reviews, and offering competitive pricing strategies are essential for enhancing consumer trust and encouraging purchase decisions on e-commerce platforms such as Tokopedia.